Dinamika dan Implikasi Jaminan Produk Halal dalam Ekonomi Syariah Global - Baihaqi, Baihaqi (Ameena Journal, 2024)
In the current era of economic globalization, the guarantee of halal products has evolved into a crucial factor in international trade and compliance with Sharia principles. The halalness of products not only meets the spiritual needs of Muslims but has also become a globally recognized quality standard that influences the purchasing decisions of millions of non-Muslim consumers. This article aims to explore and analyze the implications of halal product guarantees in the context of the global Islamic economy, focusing on international cooperation and the enhancement of global standards necessary to support integrity and trust in the halal industry. Through a qualitative research approach, this article reviews current policies, regulations, and practices related to halal certification in various countries, as well as evaluates their impact on economic growth and the integration of Islamic values into global economic activities. The findings of this study are expected to provide useful insights for policymakers, industry practitioners, and academics involved in the development and implementation of global halal product standards.